2011
DOI: 10.1007/s11999-010-1482-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Acetabular Retroversion Affect Range of Motion after Total Hip Arthroplasty?

Abstract: Background Increasingly, acetabular retroversion is recognized in patients undergoing hip arthroplasty. Although prosthetic component positioning is not determined solely by native acetabular anatomy, acetabular retroversion presents a dilemma for component positioning if the surgeon implants the device in the anatomic position. Questions/purposes We asked (1) whether there is a difference in ROM between surface replacement arthroplasty (SRA) and THA in the retroverted acetabulum, and (2) does increased femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Widmer and Zurfluh [ 3 ], by using a mathematical model, showed that the safe zone of cup placement varies, depending on stem version, highlighting the importance of stem anteversion. A compensatory increase of stem anteversion is also advocated by Incavo et al [ 32 ], to avoid impingement and acetabular uncoverage in patients with retroverted acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…Widmer and Zurfluh [ 3 ], by using a mathematical model, showed that the safe zone of cup placement varies, depending on stem version, highlighting the importance of stem anteversion. A compensatory increase of stem anteversion is also advocated by Incavo et al [ 32 ], to avoid impingement and acetabular uncoverage in patients with retroverted acetabulum.…”
Section: Discussionmentioning
confidence: 99%